The effect of different inlet geometries on laminar flow combined convection heat transfer inside a horizontal circular pipe - Mohammed H.A. (2023)
The effect of different inlet geometries on laminar air flow combined convection heat transfer inside a horizontal circular pipe has been experimentally investigated for Reynolds number range of 400-1600, and the Grashof number range from 3.12 105 to 1.72 106. The experimental setup consists of an aluminum circular pipe as a heated section with 30 mm inside diameter and 900 mm heated length (L/D = 30) with different inlet geometries. A wall boundary heating condition of a uniform heat flux was imposed. The inlet configurations used in this paper are calming sections having the same inside diameter as the heated pipe but with variable lengths of Lcalm. = 600 mm (L/D = 20), Lcalm. = 1200 mm (L/D = 40), Lcalm. = 1800 mm (L/D = 60), Lcalm. = 2400 mm (L/D = 80), sharp-edged and bell-mouth. It was found that the surface temperature values for calming section length corresponding to (L/D = 80) were higher than other inlet geometries due to the lower mass flow rate and higher flow resistance. It was also observed that the Nusselt number values for bell-mouth inlet geometry were higher than other inlet geometries due to the differences in the average temperatures and densities of the air. The average heat transfer results were correlated with an empirical correlation in terms of dependent parameters of Grashof, Prandtl and Reynolds numbers. The proposed correlation was compared with available literature and it shows reasonable agreement. 2008 Elsevier Ltd. All rights reserved.